Analisis Data Panel Pengaruh Investasi, Belanja Daerah Dan Unit Usaha Terhadap Penyerapan Tenaga Kerja Di Wilayah Eks Karesidenan Surakarta Tahun 2006-2014 - Alfiani, Rina; , Muhammad Arif, SE, M.Ec, Dev (2017)
The main factor driving the development of one of them is labor, so the direct absorption of energy into a very fundamental factor in the formation of economic growth. This study aimed to analyze the employment and factors that berpengaruhinya in the Ex-Surakarta. Basing on the literature and library foundation investment variables, shopping areas and business units are factors that affect employment. This research is in the form of quantitative analysis and time series data (time series) between the years 2006-2014. In accordance with the procedure pemeilihan models, the panel regression can best be used in this study is a model Fixed Effect Model. The results showed that in partial areas of investment and expenditure variable positive and significant effect on employment in the degree of error of 5%, while the business unit variable is not statistically significant effect on employment in the Ex-Surakarta. Keywords: employment, investment, shopping areas and business units.